2021
DOI: 10.1177/0963662521989191
|View full text |Cite
|
Sign up to set email alerts
|

Call them COVIDiots: Exploring the effects of aggressive communication style and psychological distance in the communication of COVID-19

Abstract: This study examined the influences of perceived distance to communicator on the effects of aggressive style (i.e. personal attacks and intense languages) in communicating scientific issues such as COVID-19 to the public. With a multi-site experiment ( N = 464), we found that aggression led to a heightened violation of expected social norm regarding communication styles. However, the interpretation of violation varied depending on the individual’s perceived distance to the communicator. Close distance articulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…This is not representative of the gender split within the wider population, nor is it racially representative. Nevertheless, while the results are not representative of the general population, the reported vaccination intent (75%) is somewhat consistent with other reports of vaccination intent across the literature ( Sherman et al, 2021 ; Chu et al, 2021 ; Malik et al, 2020 ). Additionally, two of our measures (perceived susceptibility and peer influence) demonstrated poor internal consistency.…”
Section: Strengths Limitations and Future Researchsupporting
confidence: 85%
“…This is not representative of the gender split within the wider population, nor is it racially representative. Nevertheless, while the results are not representative of the general population, the reported vaccination intent (75%) is somewhat consistent with other reports of vaccination intent across the literature ( Sherman et al, 2021 ; Chu et al, 2021 ; Malik et al, 2020 ). Additionally, two of our measures (perceived susceptibility and peer influence) demonstrated poor internal consistency.…”
Section: Strengths Limitations and Future Researchsupporting
confidence: 85%
“…In this sense, scientific communication walking pari passu with basic research is as important as closing country borders to contain the spread of the disease. 44 Furthermore, vulnerable groups and others deprived of basic needs, such as fresh water, and who are living and sleeping in the same rooms, or on the streets, have different problems and require special communication. They need to be treated in a specific way that preserves their rights and allows them to survive in the pandemic times.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, scientific communication walking pari passu with basic research is as important as closing country borders to contain the spread of the disease. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous surveys (1), we found that the majority of respondents were adherent to SDIS guidelines. During the COVID-19 pandemic, community leaders expressed frustration and dismay at people violating social distancing guidelines, using pejoratives such as "Covidiot" to label these individuals (40). Although public shaming has long played a role in the regulation of societies and can effectively inhibit some forms of socially disruptive behavior (41), public shaming during a pandemic adds a layer of stress on an already distressed public.…”
Section: Discussionmentioning
confidence: 99%